Morphological and mitochondrial changes in murine choroid plexus epithelial cells during healthy aging - Scarpetta, Valentina; Torres, Felipe Bodaleo; Salio, Chiara; Agarwal, Amit; Sassoè-Pognetto, Marco; Patrizi, Annarita (Fluids and barriers of the CNS, 2023)
Choroid plexuses (ChPs) are intraventricular structures mainly composed by specialized epithelial cells interconnected by tight junctions that establish the blood-cerebrospinal fluid (CSF) barrier. ChPs are essential to produce CSF and transport solutes from and into the brain. Deterioration of ChP function and morphology has been correlated to worsening of neurodegenerative disorders. We here map morpho-functional changes in the ChP epithelial cells during healthy aging, starting from young adult to 2-years old mice.